Studies on the Relationship of Cineole Content of the Oil and Stomata Characters of Eucalyptus Hybrid (E. tereticornis) Leaf - Bisen, S. S.; Prabhu, V. V.; Theagarajan, K. S. (Indian Forester, 1984)
Eucalyptus hybrid is grown on a large scale throughout the country mainly as pulpwood and to some extent as fuelwood. The leaves of Eucalyptus hybrid go to waste at present even-through they yield essential oil containing pinenes, cineole and other aromatic chemicals. Earlier investigations showed that some of the trees yield 'cineole-rich' oil resembling that of E. globulus (blue gum). As they are morphologically indistinguishable from others, a simple and rapid test based on the relationship between refractive index and cineole content of the oil was developed to distinguish these trees from others The results of preliminary studies under light microscope supported by SEM or the epidermal features of the leaves indicate that stomatal characters such as stomatal frequency, wax plugging and raticulate cuticle can serve as useful criteria for differentiating cineole-rich ones from others. Lesser number of stomata per unit area appears to be the most important characteristic of a 'cineole-rich' leaf. This will permit screening, using equipment like LM that could be set up more easlly in the field without the need of a distillation unit and its necessary heating arrangement.